#TITLE_ALTERNATIVE# - DEBBY NURSASTRADININGRUM (NIM : 151090740); Pembimbing : Dr. Ir. Agung Budi Harto, M.Eng.; Dr.
Citarum is the largest river in West Java that has considerable influence over sociopolitical and economic aspects of the region over the last 16 centuries, dating back to the Tarumanagara Kingdom. Historians believe that Batujaya site, one of TarumanagaraÃ‚Â’s most prominent legacies, was built on the mouth of Citarum. Due to physical changes, however, Batujaya has shifted and is currently located about 500 meter north of Citarum. Unfortunately, to date, there is no comprehensive study about the evolution of Citarum river other than from archaeological perspective. This research, wherefore, aims to identify the physical changes occurred upon Citarum using spatial and geomorphic approaches by utilizing 3 types of map: US Army map, RBI map, and geologic map covering the period between 1962 to 2001. Since the three kinds of map are distinct in coverage, format, and horizontal datum, several processes, such as map clipping, map digitizing, and datum transformation, need to be executed so the analysis can be performed objectively. After the analysis, it can be concluded that there is a significant change as the coastal line expanded outward, mainly due to vastly increased sedimentation, there are also rapid land cover changes in the period of interest, where paddy field and fish pond remain the dominant features and also sizable reduction of mangrove and nipa palm. Based on geomorphic analysis, Batujaya was built in a point bar of Citarum floodplain. As the point bar widens over the years, Batujaya is now located further away from Citarum.